Analysis Of Improving The Quality Of DHF Case Documentation With Clinical Documentation Improvement (CDI) At Jasa Kartini Hospital: Analisis Peningkatan Kualitas Dokumentasi Kasus DHF Dengan Clinical Documentation Improvement (CDI) Di Rumah Sakit Jasa Kartini - Nabila, Meuthia Jasmine; Kurniasih, Dewi Lena Suryani (Jurnal Rekam Medis dan Informasi Kesehatan, 2025)
Accurate clinical documentation is an important foundation in providing quality health services. Incomplete clinical documentation can cause coding errors. One of the efforts made is to improve clinical documentation to improve the quality of documentation. The purpose of this study was to determine how the documentation was before CDI was implemented and the hospital's needs for CDI implementation. The study used a mixed method with sequential explanatory designs, the implementation of the first stage of the study used qualitative by conducting interviews with 3 informants followed by quantitative by assessing the clarity, consistency, and accuracy of DHF cases in inpatient patients with a total sampling of 52 files. The results showed that outpatient documentation had used RME, while inpatient care was still a combination because it was in the electronic signature development stage. There was no SOP regarding CDI so that CDI was not understood by all officers. Of the 52 files, there was an unclear diagnosis in 18 files (35%), inconsistency in writing in 5 files (10%), and inaccuracy in 1 file (2%). The implementation of the three components has not reached 100%. The coder's understanding of coding and reconfirming with the doctor is very necessary. The implementation of CDI is needed and can be one of the improvements in the quality of documentation that plays a role in improving the quality of service.